Pengaruh Kesadaran Perpajakan dan Peran Pemerintah dalam Mengedukasi Kepatuhan Pajak Terhadap Pelaku UMKM (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Low tax compliance among UMKM remains a significant issue, even though many business actors have already registered and obtained a Taxpayer Identification Number (NPWP). This condition is influenced by several factors, including limited understanding of tax regulations, insufficient government support, and the prevalence of illegal levies that are often mistaken for official tax obligations. These issues not only increase operational costs but also reduce trust in the tax system among UMKM actors. This study aims to analyze the effect of tax understanding and the role of government on tax compliance among UMKM in West Java Province. An explanatory survey method was employed, involving 49 UMKM respondents. Data were collected through electronic questionnaires supported by observations and direct interviews. The results indicate that tax understanding has a positive and significant effect on UMKM tax compliance, with a significance value of 0.000 (p < 0.05). Additionally, the role of government also shows a positive and significant influence on UMKM tax compliance, with a significance level of 0.039. These findings highlight the importance of improving tax education, providing continuous assistance after NPWP registration, and enhancing transparency in government services to encourage voluntary tax compliance among UMKM.